Successful Cross-circulation Stent-Retriever Embolectomy Through Posterior Communicating Artery for Acute MCA Occlusion by Using Trevo XP ProVue - Seul Kee Kim; Byung Hyun Baek; Tae Wook Heo; Woong Yoon (Neurointervention, 2016)
Acute ischemic stroke due to embolic occlusion of the middle cerebral artery (MCA) in patients with chronic ipsilateral internal carotid artery (ICA) occlusion is quite rare. Several previous reports demonstrated that intra-arterial (IA) thrombolytic therapy or aspiration thrombectomy using the cross-circulation technique via an alternative collateral pathway is feasible in acute stroke patients with an unfavorable direct route to the occluded sites. However, stent-retriever embolectomy via the cross-circulation approach has not been reported in the literature. The present paper reports the first case of successful stent-retriever embolectomy for acute MCA occlusion via the patent posterior communicating artery (PComA) by using Trevo XP ProVue stent-retriever in a patient with acute MCA stroke and chronic occlusion at the origin site of the ipsilateral ICA.